2018
DOI: 10.1002/jlb.mr1117-469r
|View full text |Cite
|
Sign up to set email alerts
|

Follicular regulatory T cell in atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease involving the infiltration of immune cells, such as monocytes/macrophages, neutrophils, T cells, and B cells, into the inner layer of vessel walls. T and B cell functions in the process of atherogenesis, as well as their mutual regulation, have been investigated but several aspects remain to be clarified. In the present review, we give a brief overview of the functions of follicular regulatory T cell (Tfr) on follicular T (Tfh) and B cell regulation related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 92 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…Additionally, the results demonstrated that angiography and its related variable factors such as X ray had no effects on the IL 10 pro duction and it may confirm the safety of the angiography protocol. In parallel with our results it has been reported that number and functions of T regulatory cells decreased in the atherosclerotic patients [11]. T regula tory cells are the main source of IL 10 [10], hence, due to our results, it appears that down regulation of IL 10 may be related to the decreased umber and functions of T regulatory cells in the patients.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the results demonstrated that angiography and its related variable factors such as X ray had no effects on the IL 10 pro duction and it may confirm the safety of the angiography protocol. In parallel with our results it has been reported that number and functions of T regulatory cells decreased in the atherosclerotic patients [11]. T regula tory cells are the main source of IL 10 [10], hence, due to our results, it appears that down regulation of IL 10 may be related to the decreased umber and functions of T regulatory cells in the patients.…”
Section: Discussionsupporting
confidence: 91%
“…Although sharing nearly identical receptors with Tfh cells, Tfr cells, which are derived from Treg cells exert a potent inhibitory effect that suppress excessive Tfh cell expansion, B cell response and antibody production to orchestrate germinal center (GC) cell dynamics [17][18][19] . Growing evidence has shown that the dysregulations of Tfr cells including quantity and quality anomalies, as well as the imbalance of Tfh/Tfr cells, are implicated in various immune diseases, such as autoimmunity, chronic inflammatory disease, malignancy, and transplant rejection [19][20][21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, follicular regulatory T cells (Tfr) are an effector subset of regulatory T cells (Treg), which control GCs cell number and Tfh function but have varied effects on the quality and antigen specificity of the response [10][11][12][13][14]. Studies suggest that partial or temporary disruption of Tfr function leads to increased availability of costimulatory molecules and increase in the antigen-specific immune response [15][16][17][18]. Accumulating evidence has demonstrated that circulating Tfr (cTfr) and Tfh (cTfh) have been found in blood and display phenotypic and functional feature of classical Tfr and Tfh [19][20][21].…”
Section: Introductionmentioning
confidence: 99%